Revisiting and rethinking contemporary urban design - Samalavicius, Almantas (Journal of Architecture and Urbanism, 2013)
Professor, Doctor Almantas Samalavicius interview with Nikos Salingaros, professor of mathematics at Texas University Urban and architectural theorist Nikos Salingaros, a professor of mathematics at Texas University, San Antonio is affiliated with departments of urbanism in several countries and has made a significant contribution to the understanding of urban planning on a human scale. His important books on various issues in urban and architectural theory are well-known to all members of the profession and academy, especially those seeking for the application of scientific principles in urbanism. Nikos Salingaros has contributed significantly to the New Athens Charter (2003) – an important yet largely neglected document providing timely guidelines for reshaping present mainstream urbanism that still remains under the spell of urban ideology coined by Le Corbusier, Giedion and legions of their followers. A critic of Corbusian doctrines as well as more recent tendencies of urbanism based on stale legacy of Modernism, Nikos Salingaros offers a different approach to the interpretation of contemporary cities and complexity of their functions. He is among those scholars and practitioners who firmly support the principles of urban design promoted by members of the movement known as New Urbanism. Our talk with Nikos Salingaros revolved around the issues of the need to reconsider and reshape our present attitudes prevailing in urbanism.